A dual micro-CT system for small animal imaging - Badea, C.T. (2008)
Micro-CT is a non-invasive imaging modality usually used to assess morphology in small animals. In our previous work, we have demonstrated that functional micro-CT imaging is also possible. This paper describes a dual micro-CT system with two fixed x-ray/detectors developed to address such challenging tasks as cardiac or perfusion studies in small animals. A two-tube/detector system ensures simultaneous acquisition of two projections, thus reducing scanning time and the number of contrast injections in perfusion studies by a factor of two. The system is integrated with software developed in-house for cardio-respiratory monitoring and gating. The sampling geometry was optimized for 88 microns in such a way that the geometric blur of the focal spot matches the Nyquist sample at the detector. A geometric calibration procedure allows one to combine projection data from the two chains into a single reconstructed volume. Image quality was measured in terms of spatial resolution, uniformity, noise, and linearity. The modulation transfer function (MTF) at 10% is 3.4 lp/mm for single detector reconstructions and 2.3 lp/mm for dual tube/detector reconstructions. We attribute this loss in spatial resolution to the compounding of slight errors in the separate single chain calibrations. The dual micro-CT system is currently used in studies for morphological and functional imaging of both rats and mice.